Análise bioecológica da qualidade de vida do idoso: considerações sobre o microssistema familiar - Machado, Fernanda Ribeiro (2010)
This paper presents theoretical review and empirical research on the interference of family relationships in the life´s quality of the elderly. It was adopted as reference the concepts of Bronfenbrenner s Systemic Ecological Theory. The presentation of the study used as guidelines for publication the rules required by the Journal Psicologia: Reflexão & Crítica. Chapter 1 presents a theoretical review carried out by taking as a starting point bibliographical investigation related to the themes: Bio-ecological theory of Bronfenbrenner, quality of life, family relationships and aging. In Chapters 2 and 3, we have the papers on field research conducted with older people and their families. It was found that the relationships within the family micro-system consist in a fundamental aspect for building quality of life for the elderly.